2022
DOI: 10.1111/hsc.13776
|View full text |Cite
|
Sign up to set email alerts
|

Improving patient well‐being in the United States through care coordination interventions informed by social determinants of health

Abstract: Health and well‐being are promoted when primary care teams partner with patients and provide care coordination to mitigate risks and promote optimal health. Identification of patients for care coordination is typically based on claim‐driven risk assessments. Evidence shows that social determinants of health (SDOH) drive risk for adverse health outcomes but are omitted from existing risk tools. Missed opportunities for care coordination contribute to increased healthcare costs, poorer health outcomes and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…There is existing literature confirming the association between SDoH and gaps in CC primarily for CSHCN (Miller et al, 2019; Mirza et al, 2022; Singer & Porta, 2022). Our study adds to the literature in that it shows SDoH is associated with CC gaps among non-CSHCN children, a finding that has not been widely reported.…”
Section: Discussionmentioning
confidence: 98%
“…There is existing literature confirming the association between SDoH and gaps in CC primarily for CSHCN (Miller et al, 2019; Mirza et al, 2022; Singer & Porta, 2022). Our study adds to the literature in that it shows SDoH is associated with CC gaps among non-CSHCN children, a finding that has not been widely reported.…”
Section: Discussionmentioning
confidence: 98%
“…Benefits achieved through care coordination include reduced hospital stays, lower cost of inpatient care, reduced usage of inpatient services, and higher satisfaction for individuals (Berry et al, 2013). Because of its comprehensive nature, care coordination is also being recognized as an effective strategy in identifying and addressing SDOH (Francis et al, 2018; Singer & Porta, 2022). For case managers, this is both an inspiration and a call to greater awareness and action.…”
Section: Extending the Reach Of Care Coordinationmentioning
confidence: 99%
“…A review of care coordination models with social services identified variability in target populations and services (Albertson et al, 2021). Although early results of enhanced care coordination suggest promise for improved patient well-being and reductions in key social determinants of health (SDoH) barriers (Bradley et al, 2018; Singer & Porta, 2022), this field is still emerging and significant literature gaps remain related to rural settings. Developing a more contextually relevant understanding of the rural care coordination setting is critical.…”
mentioning
confidence: 99%